(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Formation of didactic play in young children. The game is the leading activity of a preschool child, determining his further mental development, primarily because the game is inherent in an imaginary situation. Thanks to her, the child learns to think about real things and real actions.